Indole-3-carbinol improves neurobehavioral symptoms in a cerebral ischemic stroke model - Paliwal P.; Chauhan G.; Gautam D.; Dash D.; Patne S.C.U.; Krishnamurthy S. (My University, 2025)
Stroke is one of the most common causes of death worldwide and also responsible for permanent disability. Ischemic stroke has been found to affect 80% of stroke patients. Recombinant tissue plasminogen activator (rtPA) is the widely used drug for the ischemic stroke with narrow therapeutic window. Indole-3-carbinol (I3C) is a natural compound obtained from brassica species having antithrombotic activity. Middle cerebral artery occlusion (MCAO) model was used followed by reperfusion after 2 h of ischemia for the evaluation of the I3C against ischemic stroke. After reperfusion, I3C (12.5, 25, and 50 mg/kg) was given by oral route once daily and continued up to the 14th day. Behavioral studies including postural reflex, forelimb placing, and cylinder tests showed I3C attenuated the MCAO-induced increase in average score and asymmetry score efficiently. Mean cerebral blood flow (CBF) was improved by treatment with I3C (12.5 mg/kg) by 60% of baseline at 6 h. I3C inhibited ADP-induced platelet aggregation and reduced ischemic volume significantly. It also inhibited in vitro the ADP-induced platelet aggregation in healthy human volunteers. I3C improves behavioral scores and mean CBF after focal cerebral ischemia in rats. Furthermore, I3C showed prophylactic anti-thrombotic activity against carrageenan induced tail thrombosis. Therefore, preclinical evidence points to I3C as a potential candidate for use in cerebral ischemic stroke. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.